Multidimensional behavioral responses to the implementation of BIM in construction projects: an empirical study in China. Issue 2 (19th March 2021) - Cao, Dongping; Shao, Shiting; Huang, Bin; Wang, Guangbin
Abstract : Purpose: Despite its great potential to improve the sustainability of architectural, engineering, construction and facility management activities, the implementation of building information modeling (BIM) in many projects has failed to achieve expected benefits due to negative behavioral responses such as user resistance. This paper aims to characterize the complexity of end user's behavioral responses to BIM implementation in construction projects using a multidimensional perspective and examines how these responses are impacted by different levels of contextual factors. Design/methodology/approach: By integrating technology acceptance, resistance and adoption literature, this paper theoretically proposes a research model to characterize the associations between different dimensions of behavioral responses and different levels of contextual factors. The model is then empirically tested with survey and interview data collected from BIM-based construction projects in China. Findings: The empirical results not only validate the two-dimensional view of the behavioral responses (i.e. the dimension of support/resistance that ranges from aggressive resistance to enthusiastic support, and the dimension of actual use that ranges from non-use to high use) but also provide evidence for the prevalence of ambivalent responses such as supporting but lowly using and resisting but highly using. The empirical results also provide evidence that different levels of contextual factors generally play different roles in shaping the behavioral responses. Specifically, the dimension of support/resistance is more substantially impacted by the team-level factor while the dimension of actual use of BIM is more significantly associated with the project-level factor. Originality/value: While previous research on BIM adoption or implementation behaviors has primarily focused on investigating users' response from single-dimension perspectives such as acceptance or non-acceptance, this study represents an exploratory effort of using a two-dimensional view to characterize the complexity and ambivalence of end users' behavioral responses to the implementation of innovative technologies such as BIM in construction projects. This study also contributes to deepened understandings of how these different dimensions of behavioral responses are intricately shaped by different levels (i.e. individual-, team- and project-levels) of contextual factors in construction projects which are characterized as temporary and inter-organizational.